2015
DOI: 10.1002/mrm.25895
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic fat fraction and visceral adipose tissue fatty acid composition in mice: Quantification with 7.0T MRI

Abstract: Purpose: To develop an MRI method for quantifying hepatic fat content and visceral adipose tissue fatty acid composition in mice on a 7.0T preclinical system. Methods: MR acquisitions were performed with a multiple echo spoiled gradient echo with bipolar readout gradients. After phase correction, the number of double bounds (ndb) and the number of methylene interrupted double bounds (nmidb) were quantified with a model including eight fat components, and parametric maps of saturated, monounsaturated, and polyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…In this work, we have presented a method for the joint estimation of FAC parameter maps and confounding factors. The proposed method shares its signal model components with previously published approaches, including the 9‐peak fat model with variable‐amplitudes, field map, eddy‐current phase and R2* . Its key features are: (1) Data was acquired using bipolar readout gradients due to their higher SNR efficiency compared to unipolar readouts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we have presented a method for the joint estimation of FAC parameter maps and confounding factors. The proposed method shares its signal model components with previously published approaches, including the 9‐peak fat model with variable‐amplitudes, field map, eddy‐current phase and R2* . Its key features are: (1) Data was acquired using bipolar readout gradients due to their higher SNR efficiency compared to unipolar readouts.…”
Section: Discussionmentioning
confidence: 99%
“…MR spectroscopy (MRS) based approaches quantify the triglyceride saturation state by fitting Gaussian or Lorentzian lineshapes to the measured fat peaks of a 1 H MR spectrum . Since the distribution of fatty acids in various adipose fat compartments is potentially different, MRI‐based FAC methods that provide spatially resolved 3‐D parameter maps and incorporate information about the chemical triglyceride structure are of special interest . As the data are acquired at several discrete echo time points, MRI‐based methods are limited in terms of spectral resolution, and robust estimation of the confounder‐corrected signal model parameters can be challenging in the presence of image noise .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that it is feasible to simultaneously quantify fat content and fatty acid composition with MRI . In parallel, several preclinical studies have highlighted changes in liver fatty acid composition in NASH relative to simple steatosis .…”
Section: Introductionmentioning
confidence: 99%
“…The first part of the discussion tackles the global implementation of the technique in vivo . Then, the assessment of the colon walls and surrounding structures is discussed, as it has shown chemical compounds, mostly triglyceride resonating groups, which have been previously reported in adipose tissue, liver etc. Then, the discussion focuses on the relevance of the quantification of these spectra.…”
Section: Discussionmentioning
confidence: 99%